2018
DOI: 10.1176/appi.neuropsych.17040081
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic Characteristics of Chinese-Speaking Semantic Variant of Primary Progressive Aphasia

Abstract: Reading disorder is a recognized feature in Primary Progressive Aphasia (PPA). Surface dyslexia, characterized by regularization errors, is typically seen in the English-speaking semantic variant of PPA (svPPA). However, dyslexic characteristics of other languages, particularly logographical languages such as Chinese, remain sparse in the literature. This study aims to characterize and describe the dyslexic pattern in this group of patients by comparing the English-speaking svPPA group to the Chinese-speaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although many of these recommendations can likely also be applied to other types of trials across neurodegenerative diseases, such as lifestyle trials like World-Wide FINGERS, 72 some of these trials will come with their own unique challenges-such as a lack of suitable cross-cultural instruments measuring social cognition, language, and behavioral changes in frontotemporal dementia trials 73 as well as issues regarding the applicability of the diagnostic criteria for primary progressive aphasia subtypes across global languages, such as Chinese. 74 Last, we were unable to determine the direct effect of each criterion on the representation of diverse individuals using inferential statistics. Several factors precluded such analyses, such as the fact that some criteria were used either very infrequently or invariably (e.g., the MMSE, Table S2), as well as the fact that race/ethnicity data was not reported for each global region/country specifically, precluding any comparisons of the makeup of the study samples with a priori disease estimates in the general populations in these countries/regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of these recommendations can likely also be applied to other types of trials across neurodegenerative diseases, such as lifestyle trials like World-Wide FINGERS, 72 some of these trials will come with their own unique challenges-such as a lack of suitable cross-cultural instruments measuring social cognition, language, and behavioral changes in frontotemporal dementia trials 73 as well as issues regarding the applicability of the diagnostic criteria for primary progressive aphasia subtypes across global languages, such as Chinese. 74 Last, we were unable to determine the direct effect of each criterion on the representation of diverse individuals using inferential statistics. Several factors precluded such analyses, such as the fact that some criteria were used either very infrequently or invariably (e.g., the MMSE, Table S2), as well as the fact that race/ethnicity data was not reported for each global region/country specifically, precluding any comparisons of the makeup of the study samples with a priori disease estimates in the general populations in these countries/regions.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we only focused on Aβ and tau trials in this review. Although many of these recommendations can likely also be applied to other types of trials across neurodegenerative diseases, such as lifestyle trials like World‐Wide FINGERS, 72 some of these trials will come with their own unique challenges—such as a lack of suitable cross‐cultural instruments measuring social cognition, language, and behavioral changes in frontotemporal dementia trials 73 as well as issues regarding the applicability of the diagnostic criteria for primary progressive aphasia subtypes across global languages, such as Chinese 74 . Last, we were unable to determine the direct effect of each criterion on the representation of diverse individuals using inferential statistics.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 48 - 53 For Chinese speakers with ADOD including PPA, a handful of case studies suggest that patients present with language impairments reported in other languages—specifically difficulties with word fluency, processing action and object pictures and acquired dyslexia. 54 - 61 However, the patterns of aphasia are not always identical to the symptoms reported in patients from other cultures. 62 There will of course also be cultural and linguistic differences between Mainland Chinese speakers with ADOD who speak different dialects and languages.…”
Section: Dementia In Greater Chinamentioning
confidence: 80%
“…Mandarin speaking patients who have PPA in Singapore (a multilingual linguistic environment) show an unexpected tendency to produce a pattern of semantic reading errors referred to as deep dyslexia in Indo-European languages. [57][58][59] Deep dyslexia is not typically found in PPA in these languages wherein phonological and surface dyslexia or dysgraphia are more commonly reported. 88 There is evidence that Chinese speakers with PPA present a mixture of deep and surface dyslexia suggesting a heterogeneity in symptoms possibly due to the complexity of the Chinese writing system.…”
Section: Aphasia In Chinese Speakers With Adod Including Ppamentioning
confidence: 99%
“…(3) Semantic errors: Semantic errors occur when the output and target characters are semantically related ( 15 , 30 ), such as the confusion of “刷” (shuā/brush) and “扫” (sǎo/sweep) ( 10 ).…”
Section: Resultsmentioning
confidence: 99%